Different Tillage Systems Affect Plant Emergence, Stand Establishment and Yield in Wheat-Corn Rotation - Barut, Zeliha B.; Celik, Ismail (2010)
In this study, we compared the conventional and conservation tillage systems in terms of their effects on plant emergence and stand establishment. The systems consisted of conventional tillage with stubble burning (CT1), conventional tillage with stubble (CT2), minimum tillage with stubble (MT), combination of minimum and no tillage (MNT) and notillage (NT). The tillage treatments were used for Balatilla domestic wheat (Triticum aestivum L.) and Pioneer Brand corn (Zea mays L.) cultivars under crop rotation. Mean emergence day (MED), emergence rate index (ERI), percentage emergence (PE), multiple index (MI), skip index (SI), quality of feed index (QFI), mean spacing between plants for corn and plant density for wheat were evaluated for uniformity of plant emergence and stand establishment. ERI and PE were significantly higher under CT and MT compared with MNT and NT treatments in corn. Plant emergence in conventional tillage plots occurred faster with over 95% emergence. Tillage treatments also affected SI, QFI and mean plant spacing, but not MI. The best SI, QFI and plant spacing were recorded in the CT and MT treatments. Uniformity of plant stand in the tilled plots, CT and MT were better than that in no-tillage. No-till treatment had the poorest stand establishment. In wheat, the highest plant density was obtained under CT and MT treatments. Based on the average of 2 yr, the highest yield of wheat was obtained under CT and the lowest in NT. Corn yield had similar results. The trend in yield for both crops also followed that of the results for stand establishment and emergence parameters. The lower yield in no-till was related to the weaker plant emergence and stand establishment. The comparable effect of MT with CT suggests that MT can be an alternative tillage method for sustainable agriculture.
Keywords: Wheat--Yields.